(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The purpose of this article is to strengthen the foundations of national identity, to modernize our national code by studying our sacred places and culture, to systematize found places on the territory of Kazakhstan with a view to acquaintance and demonstration of the sacred places of Kazakhstan. The relevance of this article is that modern approaches to understanding the sacred places of Kazakhstan are used. The article describes and analyzes cemeteries and underground mosques in Mangistau. According to the myths preserved in Mangistau, 360 Sufis live and are buried here. Their names are mostly lost in the vast steppes of Mangistau, but among them in the memory of the people there are names such as Shopan-ata, Masat-аta, Sultan-upi аta, Karaman-ata, Shakpak-аta, Koshkar-аta, Beket-аta, etc. The local population still reveres their names and thousands of pilgrims visit sacred places to worship the saints. In this article, the above-mentioned names are regarded as holy and the reasons for their veneration among the people. Key words: Becket ata, Shopan ata, Karaman ata, Masat ata, Shakpak ata, Sultan-upi ata.